The Implementation of Maqashid Shariah Principles in the Beauty Salon Business - Awwaliyah, Rosyidatul; Rahman, Okta Fauzia; Adrina, Ressina; Putri, Fyolla Alycia (Business and Sustainability, 2023)
The beauty industry has become an important part of the modern lifestyle. However, beauty salons often face challenges in aligning their practices with sharia principles. This research discusses the salon concept based on sharia provisions, exploring the implementation of Islamic principles in beauty services. The provisions that beauty salons must have are the use of products that are halal certified. The aim of this research is to explain the level of implementation of maqashid sharia in salons. To find out how far salons consider sharia aspects in their business, this research uses a literature review and the Simple Additive Weighting (SAW) method as research methodology. The research results show that there are still many sharia-based salons but do not meet the maqashid sharia criteria.